Effects of microgravity and hypergravity on platelet functions - Dai, Kesheng; Wang, Yuedan; Yan, Rong; Shi, Quanwei; Wang, Zhicheng; Yuan, Yanhong; Cheng, Hong; Li, Suping; Fan, Yubo; Zhuang, Fengyuan (Thrombosis and Haemostasis, 2009)
Many serious thrombotic and haemorrhagic diseases or fatalities have been documented in human being exposed to micro-gravity or hypergravity environments, such as crewmen in space, roller coaster riders, and aircrew subjected to high-G training. Some possible related organs have been examined to explore the mechanisms underlying these gravity change-related diseases. However, the role of platelets which are the primary players in both thrombosis and haemostasis is unknown. Here we show that platelet aggregation induced by ristocetin or collagen and platelet adhesion to von Willebrand factor (VWF) were significantly decreased after platelets were exposed to simulated microgravity. Conversely, these platelet functions were increased after platelets were exposed to hypergravity. The tail bleeding time in vivo was significantly shortened in mice exposed to high-G force, whereas, was prolonged in hindlimb unloaded mice. Furthermore, three of 23 mice died after 15 minutes of –8 Gx stress. Platelet thrombi disseminated in the heart ventricle and blood vessels in the brain, lung, and heart from the dead mice. Finally, glycoprotein (GP) Ibα surface expression and its association with the cytoskeleton were significantly decreased in platelets exposed to simulated microgravity, and obviously increased in hypergravity-exposed platelets. These data indicate that the platelet functions are inhibited in microgravity environments, and activated under high-G conditions, suggesting a novel mechanism for gravity change-related haemorrhagic and thrombotic diseases. This mechanism has important implications for preventing and treating gravity change-related diseases, and also suggests that special attentions should be paid to human actions under different gravity conditions.
Keywords: Platelets; thrombosis; haemorrhage; simulated microgravity; hypergravity